Risk Factors for Nasal Symptoms, Olfactory Disorders and Mucociliary Transport in Factory Workers - Dewi, Anna Mailasari Kusuma; Kristyanto, Jarod Wahyu (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Occupational exposure to a variety of individual chemicals has been associated with olfactory dysfunction, which is important for many occupational groups that rely on intact olfactory function to perform their jobs and for their safety. We aim to determine the risk factors for nasal symptoms, olfactory disorders and mucociliary transport in spice factory workers in Semarang. Subjects and Method: This was a cross-sectional study. A sample of 600 factory workers filled out the NOSE Scale and QOD-NS questionnaires, having their ears, nose, and throat examined, and calculated the time in which the participants tasted sweetness after being given saccharin to the inferior turbinate. The analysis used were univariate, bivariate and multivariate analysis. Results: Of 600 respondents, 52.2% were women, 87.8% had reported no nassal symptoms, 81.5% had normal NOSE scale, and 83.3% had normal mucociliary transport. Risk factors for nasal disorders, smell disorders, and mucociliary transport disorders were age ≥40 years old, male, smoking, longer exposure time, obesity, and PPE use. Conclusion: There is a significant association between occupational risk factors and nasal symptoms, olfactory disorders and mucociliary transport disorders. The most influential factor is discipline in using PPE to prevent nasal disorders, olfactory disorders and mucociliary transport disorders.